Analisis Bibliometrik: Perkembangan Kebijakan Pengelolaan Limbah Usaha Mikro Kecil Menengah (UMKM) berbasis Circular Economy - Sabrina Hartianingrum, Hikmah; Yuadi, Imam (HIGIENE: Jurnal Kesehatan Lingkungan, 2023)
The activities of small medium enterprises (SMES) are assessed to have a significant impact on environmental conditions if not balanced by post management of post-production waste that can lead to environmental degradation. The circular economy model is considered to be a new model to replace the linear economic model. The purpose of this study was conducted to determine the development of the economic circular model used in the management policy of SMES waste. Bibliometric research method by using Vosviewer and RSTUDIO software. Sampling used in this study is a journal article with subjects related to public policy. Data are collected using the Scopus database then the data is analyzed manually to generate the relevant articles. The results showed that research has been developed massively in 2018, 7 years since the first time the research was conducted. The focus of research has been in the simplification of production and policy flow. Later, a study to achieve the innovation of the economic circular concept on the management of the SMES waste. Finally, regulations or policies in waste management significantly have linkages with attempts to achieve development goals.